LITERATURE REVIEW ON CONFUCIAN HERITAGE CULTURE IDENTITY IN MALAYSIAN CHINESE PRE-UNIVERSITY STUDENTS - Choong, Shiau Huai; Daniel, Esther Gnanamalar Sarojini; DeWitt, Dorothy (PUPIL: International Journal of Teaching, Education and Learning, 2020)
The words Confucian Heritage Culture (CHC) may bring to mind Confucianism. The words may also point to those of Chinese origin. Yes, although CHC evolved from Confucianism, yet it does not mean that it is the original Confucianism. CHC has evolved. Past literature has CHC related studies done mainly in the West and documents the achievements of CHC students (particularly Asian students). They have persistently performed well in international comparative studies of mathematics and science achievement. Nevertheless, these studies cannot be generalised, because globalisation and rapid social change has influenced and shaped the Chinese community in CHC countries, one of which is Malaysia. The present paper presents a literature review of CHC based on a larger study in search of a CHC identity among Malaysian Chinese pre-university students. The literature helped to uncover the underlying characteristics, namely respect, education and perseverance which were then incorporated within appropriate items in a survey instrument in the larger study to investigate CHC among a selected group of students. These underlying characteristics points towards a CHC identity inherent in these students. This paper will not discuss the instrument or the findings of the larger study.